Effectiveness of the Blood and Body Fluid Exposure Prevention Program among Operating Room Nurses - Dokkaew, Morakot; Kasatpibal, Nongyao; Viseskul, Nongkran (Journal of Phrapokklao Nursing College, Chanthaburi, 2023)
This quasi-experimental research aimed to study the effectiveness of the blood and body fluid exposure (BBFE) prevention program among operating room nurses. The samples consisted of 36 operating room nurses in a university hospital. The research instruments included the BBFE prevention program among operating room nurses, the demographic questionnaire, the knowledge on BBFE prevention test with a reliability of .73, the practice on BBFE prevention observation form with a reliability of 1, and the incidence of BBFE record form. The implementation and data collection were conducted from November 2020 to January 2021. Data were analyzed by frequency, percentage, mean, standard deviation, median, quartile, Wilcoxon signed-rank test, Chi-square test, and calculating incidence. The research results revealed that 1) after using the program, operating room nurses had statistically significantly higher score of knowledge on BBFE prevention than that of before using the program (Z = -4.851, p < .001); 2) after using the program, operating room nurses had statistically significantly higher proportion of correct practice on BBFE prevention than that of before using the program (χ2 = 247.956, p < .001); and 3) after using the program, operating room nurses had lower incidence of BBFE than that of before using the program. This research suggests that nurse executives should provide knowledge, demonstration and return demonstration, feedback, and personal protective equipment to operating room nurses. This will help operating room nurses improve their knowledge and practice on BBFE prevention.